Effect of defects on the fatigue limit of Ni‐based superalloy 718 with different grain sizes. Issue 5 (26th February 2019) - Kevinsanny; Okazaki, Saburo; Takakuwa, Osamu; Ogawa, Yuhei; Okita, Koichi; Funakoshi, Yusuke; Yamabe, Junichiro; Matsuoka, Saburo; Matsunaga, Hisao
Abstract: Tension‐compression fatigue tests were performed on two types of Ni‐based superalloy 718 with different microstructures in which small artificial defects of various sizes and shapes were introduced. The susceptibility of the fatigue strength to the defects varied significantly with the microstructure morphology, ie, a smaller grain size made the alloy more susceptible to defects. The fatigue limit as a small‐crack threshold was successfully predicted using the area parameter model. The evaluation of the fatigue limit was classified into the following three stages depending on the defect size: (a) harmless defect regime, (b) small‐crack regime, and (c) large‐crack regime. Such a classification enabled comprehensive evaluation of the fatigue limit in a wide range of defect size, considering (a) defect size over a range of small crack to large crack and (b) characteristics of matrix represented by grain size and hardness.